A New Transparent Way to Perform Competition, Market Structure and IPR Portfolio Analyses: Analysis of the Dynamics of Trademark Competition in Finland as a Case Example - Theresa Lauraéus; Jari Kaivo-oja (Lithuania, 2022)
The paper presents a new way to perform IPR portfolio analyses (trademark and patent analyses) and other market structure analyses. Trademark and patents analyses become more significant for the development of companies, especially in current conditions of technological disruption. We will reflect (1) current STI management and foresight, (2) most important IT technology trends for year 2017 and (3) the most evaluated technologies in the Gartner HC evaluations. Trademark analyses and especially novel LKI analysis can contribute to capturing relevant aspects of market and technology disruptions. Our demonstration is focused on trade marking and trademark registrations in Finland. The LKI analysis is scientifically as generic as Herfindahl-Hirchman Index (HHI) has been during its long history of indicator research. LKI approach makes us free from the scaling problems of conventional HHI. IPR portfolios with any size can now be analysed without potential statistical biases. We develop and introduce the HHI index and a new IPR and market analysis index: LKI (Lauraeus-Kaivo-oja Index). The evaluation results of the HHI analysis and the LKI analysis are compared. With the LKI, we are able to compare better the substance of Intellectual Property Right (IPR) portfolios and market structures. Furthermore, we show, why percentage numbers are easier to comprehend than HHI index points.